(3fXGe GdVQjHI GdehMOI Ydi GdONd heOi edGAeJg ddJWHjb aj GdOhd GdfGejI (B: s (3OQGSI JWHjbjI ddfXGe GdVQjHj GdeUQj (B/ s - (3YHO GdSdGe eMeO YHO GdSdGes; (3eMeO CMeO GdQRGRs; (3GdSjO Ydj YHO Gdehdis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1993)
(3jSJdRe GdHMK aj gPG GdehVhY GdJYQa Ydi gPG GdfXGe ef GdfGMjI GdfXQjI hef MjK eLGd GdJWHjb aj GdfXe GdVQjHjI GdebGQfI MJi fJYQa Ydi EjLGHjGJ gPG GdfXGe hSdHjGJg hcjajI JLfH Jdc GdSdHjGJ aj efGN edGFe ddJWHjb dfJhUd Edi eOi edGFeJg ddJWHjb aj GdOhd GdfGejI hdPdc fLO Cfg ef GdGRe GdJYQa Ydi eHQQGJ GdCNP HfXGe GdVQjHI GdehMOI aj eUQ heYhbGJ GdJWHjb, hgPG jYfj VQhQI GdJYQa Ydi GdONd aj eUQ, hjSJdRe Pdc CjVG VQhQI GdJYQa Ydi Jchjf hYGA GdVQjHI GdehMOI aj eUQ(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdeGdjI GdYGeI hGdJTQjY GdVQjHj (B1993.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B469-491.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdVQGFHs; (3GdYQGbs -- (3bhGfjf hJTQjYGJs; (3ShQjGs -- (3bhGfjf hJTQjYGJs; (3GdCQOfs -- (3bhGfjf hJTQjYGJs; (3GdVQGFH GdfhYjI s; (3GdVQGFH GdehMOI s; (3GdLgGR GdVQjHjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjY GdVQjHjs